2017
DOI: 10.1371/journal.pone.0169706
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric CO2 concentration effects on rice water use and biomass production

Abstract: Numerous studies have addressed effects of rising atmospheric CO2 concentration on rice biomass production and yield but effects on crop water use are less well understood. Irrigated rice evapotranspiration (ET) is composed of floodwater evaporation and canopy transpiration. Crop coefficient Kc (ET over potential ET, or ETo) is crop specific according to FAO, but may decrease as CO2 concentration rises. A sunlit growth chamber experiment was conducted in the Philippines, exposing 1.44-m2 canopies of IR72 rice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 31 publications
(50 reference statements)
1
10
0
Order By: Relevance
“…In predicted future higher CO 2 climates, it has been suggested that plants will be more water-use efficient as enhanced photosynthetic A allows stomata to be less open, meaning less water will be lost (Keenan et al, 2013). However, despite grain yields increasing in experiments where rice is grown at elevated CO 2 , a greater volume of water is used than at current CO 2 levels, indicating that, in the future, rice cultivation may be even more water intensive than it is today (Kumar et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In predicted future higher CO 2 climates, it has been suggested that plants will be more water-use efficient as enhanced photosynthetic A allows stomata to be less open, meaning less water will be lost (Keenan et al, 2013). However, despite grain yields increasing in experiments where rice is grown at elevated CO 2 , a greater volume of water is used than at current CO 2 levels, indicating that, in the future, rice cultivation may be even more water intensive than it is today (Kumar et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Rising CO 2 levels are expected to result in a warming of 1-4°C in global atmospheric temperatures by the end of the century, and the frequency of heat spikes will also increase (Meyer et al, 2014). Such dramatic rises in temperature are expected to lead to negative impacts on rice yields even in the presence of increased atmospheric CO 2 (Ainsworth, 2008;Kumar et al, 2017). Rice is particularly sensitive to heat stress, with the majority of growth stages being affected once temperatures exceed 35°C (Redfern et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Elevated [CO 2 ] typically decreases stomatal conductance, resulting in a decrease in ET and increase in canopy temperature (T c ) for rice (Shimono, Nakamura, Hasegawa, & Okada, 2013;Yoshimoto, Oue, & Kobayashi, 2005) and other crops (Leakey et al, 2009 and references therein). However, Kumar, Quick, Barrios, Sta Cruz, and Dingkuhn (2017) recently reported an increase in ET from a rice canopy under elevated [CO 2 ]. These different results suggest that further research is still necessary on how energy balance in a rice canopy changes in response to elevated [CO 2 ] conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, alternative approaches that support limited data are needed, which has led to a large number of related studies applied to various climatic conditions. Evapotranspiration, regardless of evaluated spatiotemporal scale, is extremely variable, because it is driven by the evaporative demand of the atmosphere (Kumar et al, 2017). This feature justifies the knowledge of its dynamics in a delimited geographical area, as these are areas of federal units, the states.…”
Section: Introductionmentioning
confidence: 95%
“…In agreement with Allen et al (1998), these characteristics would be similar to the evapotranspiration of an extensive grass surface, with uniform height, which grows actively, totally shadows the soil without any water limitation. This hypothetical condition is known as reference evapotranspiration (ETo), and when multiplied by a specific crop coefficient (kc), satisfactorily estimates the water demand of a plant community, since it normalizes the ET observed in variable climatic conditions (Kumar et al, 2017). In the last decades, several methods were developed to estimate ETo (Penman, 1948;Blaney and Criddle, 1950;Makkink, 1957;Turc, 1961;Priestley and Taylor, 1972;Hargreaves and Samani, 1985;Oudin et al, 2005).…”
Section: Introductionmentioning
confidence: 99%